Features of the SPINK5 gene polymorphism associations with food allergy onset and course in children - O. P. Pakholchuk (Zaporožskij Medicinskij Žurnal)
Resume. It is less known about role of the genetically predisposing factors in the onset and course of the food allergy (FA).